Guidance strategies for writing scientific articles based on international journals in indonesian language learning for nursing students - Moh. Zainudin; Eka Nurjanah (Jurnal Konseling dan Pendidikan, 2025)
The objectives of this research were: 1) To describe guidance strategies in writing article scientific. 2) Exploring challenges faced student in the process of tracing and utilization reference journal international reputable. 3) Analyze the processes carried out student in paraphrasing and compiling argument based on reference journal international. Research methods This used method qualitative. Research data sources was undergraduate nursing student a total of 12 students who fulfilled the requirements criteria inclusion. Data collection techniques, namely with semi-structured interviews, questionnaires observation and documentation. Data analysis techniques used that was data reduction, data presentation, and data extraction conclusion. Findings study This were: 1) Guidance strategy lecturer contribute positive to understanding student in compile structure article scientific conceptual. Giving example template help student understand and apply systematics writing in a way more directed. 2) Students face challenge in explore and utilized journal international reputable, especially related limitations access beginning and obstacles language. However, guidance lecturer through keyword utilization as well as use of platforms such as ScienceDirect and tools help digital translation helped student overcome obstacle the in a way gradually. 3) Ability paraphrasing and compiling argument student develop through guidance directly, with an approach that included reading strategies navigation, used Language Alone For avoid plagiarism, as well as pattern argumentative in the form of presentation of data/facts, interpretation, comparison and association with relevant theory.